VARIASI INDIVIDU TERHADAP KUALITAS SEMEN SEGAR KALKUN (Individual Variation in Turkey’s Fresh Semen Quality) - Rahmi, Annisa; Haryanto, Agung Puji; Adistya, Firly; Arasya, Adiba Kanza; Baharun, Abdullah (Universitas Nusa Cendana, 2025)
Turkey is a kind of poultry with a special meat taste and higher meat protein than other poultry meat. Indonesia have limited turkey’s population because they has problem in reproduction efficiency is significant different in body weigh between male and female. Artificial insemination practices can be a solution for turkey’s reproduction efficiency problem. However, artificial insemination needs spermatozoa with good quality to fertilize the ovum. The individual gobbler (male turkey) could produce semen with different quality even though kept in same environtment condition. This study aim to evaluate individual variation impact to turkeys fresh semen quality. The fresh semen collected from 4 turkeys bronze breed in 8-12 months age, with massage technique two times a week. The macroscopic (volume, pH, colour, consistency) and microscopic (concentration, motility, viability, abnormality) examination become the observed variables. The result shows there are individual variation in variables are volume, pH, and sperm concentration from fresh semen. The result of this study can provide basic information about turkey’s fresh semen quality with individual variation.